Samm50 Promotes Hypertrophy by Regulating Pink1-Dependent Mitophagy Signaling in Neonatal Cardiomyocytes - Xu, Ran; Kang, Le; Wei, Siang; Yang, Chunjie; Fu, Yuanfeng; Ding, Zhiwen; Zou, Yunzeng (Frontiers in Cardiovascular Medicine, 2021)
Pathological cardiac hypertrophy, the adaptive response of the myocardium to various pathological stimuli, is one of the primary predictors and predisposing factors of heart failure. However, its molecular mechanisms underlying pathogenesis remain poorly understood. Here, we studied the function of Samm50 in mitophagy during Ang II-induced cardiomyocyte hypertrophy via lentiviruses mediated knockdown and overexpression of Samm50 protein. We first found that Samm50 is a key positive regulator of cardiac hypertrophy, for western blot and real-time quantitative PCR detection revealed Samm50 was downregulated both in pressure-overload-induced hypertrophic hearts and Ang II-induced cardiomyocyte hypertrophy. Then, Samm50 overexpression exhibits enhanced induction of cardiac hypertrophy marker genes and cell enlargement in primary mouse cardiomyocytes by qPCR and immunofluorescence analysis, respectively. Meanwhile, Samm50 remarkably reduced Ang II-induced autophagy as indicated by decreased mitophagy protein levels and autophagic flux, whereas the opposite phenotype was observed in Samm50 knockdown cardiomyocytes. However, the protective role of Samm50 deficiency against cardiac hypertrophy was abolished by inhibiting mitophagy through Vps34 inhibitor or Pink1 knockdown. Moreover, we further demonstrated that Samm50 interacted with Pink1 and stimulated the accumulation of Parkin on mitochondria to initiate mitophagy by co-immunoprecipitation analysis and immunofluorescence. Thus, these results suggest that Samm50 regulates Pink1-Parkin-mediated mitophagy to promote cardiac hypertrophy, and targeting mitophagy may provide new insights into the treatment of cardiac hypertrophy.